Determination of melphalan in human plasma by UPLC-UV method - Huang, Liusheng (Cancer Chemother Pharmacol, 2019)
It is desirable to develop a fast method for quantification of melphalan due to its instability. Here we report a method for quantification of melphalan (MPL) in human plasma using a UPLC-PDA system. Briefly, 50 µL plasma sample was mixed with 25 µL internal standard (2500 ng/mL acetylmelphalan in methanol) and 25 µL 20% trichloroacetic acid, and centrifuged at 21,000 g (15,000 rpm) at 4 °C for 3 min. The supernatant (5 µL) was injected onto an Acquity™ BEH C18 LC column (2.1 × 50 mm, 1.7 µm) and eluted with 25 mM NH(4)AC (pH 4.7) - acetonitrile in a gradient mode at a flow rate of 0.6mL/min. The column kept at 40±5 °C and the autosampler kept at 4±5 °C. The detector set at 261 nm, and sampling rate was 40points/sec. The retention times were typically 2.11 min for melphalan and 2.38 min for the internal standard. Total run time is 4 min per sample. Calibration range was 100–40,000ng/mL. The lower limit of quantification was 100ng/mL. The method was validated based on the FDA guidelines, and applied to a clinical pharmacokinetic study in pediatric patients.